Estimation of spatio-temporal vegetation trends in different land use environments across Greece. Issue 1 (2nd January 2019) - Banti, Maria Α.; Kiachidis, Kyriakos; Gemitzi, Alexandra
ABSTRACT: Our work deals with the estimation of spatio-temporal vegetation trends in various land use types in a typical Mediterranean country like Greece. Analysis of vegetation during all seasons was performed using remotely sensed Normalized Difference Vegetation Index (NDVI) during 2000–2017 in conjunction with the various land use environments. Results highlighted the dominating vegetation greening all over the country during all seasons. Sporadic spots with a negative vegetation trend were observed in areas that had experienced fire events. Forests and semi-natural areas, characterized by absence of human activities, demonstrated the highest greening vegetation pattern, indicating thus the possible climate change implications. Urban areas, representing the land portions mostly influenced by human interventions, showed a greening pattern, attributed to a combination of increased temperature and CO2 in those areas, but also highlighted the possible positive environmental footprint of economic recession period that Greece is undergoing during the last decade. Graphical Abstract: